From speech acts to communicative acts: social network debates about sexual consent - Torras-Gómez, Elisabeth; Krauchenberg, Arja; Petuya, Victor; Marcos, Rebeca; Serradell, Olga; Soler-Gallart, Marta (Frontiers in Sociology, 2025)
IntroductionUnderstanding consent is essential to combat sexual violence, a deeply rooted social problem. Amidst its complexities, the scientific literature has emphasized the shortcomings of only considering the speech act—whether the victim-survivor said “yes” or not. Instead, sociological research underscores the need to analyze the whole communicative act where different elements lead to either a power relationship where there is no consent or a dialogic relationship where freedom is granted. Although some research has been conducted on citizens’ social media debates on consent, how such debates include the concept of communicative acts to discuss it has not been analyzed yetMethods55 gender-related Instagram and Twitter (now known as X) posts—published and extracted over the course of 14 days—were analyzed.ResultsFindings reveal that most posts refer to Power Communicative Acts as a hindrance for consent due to hierarchical power imbalances or to coercion, and called for the need to establish elements of Dialogic Communicative Acts to achieve consent and construct more egalitarian environments. Finally, most posts that considered ethics spoke about the need for perpetrators to be held accountable or offered similar takes on consequentialism.DiscussionThese findings help illustrate how several social media debates about consent successfully fall into the Communicative Acts framework.